(untitled) (Value : Jurnal Manajemen dan Akuntansi, 2025)
Financial performance refers to a report that outlines a company’s financial condition. It serves as a basis for internal decision-making and allows the public to evaluate how effectively the company is operating. This study aims to examine the influence of intellectual capital disclosure, leverage, and company size on the financial performance of banking institutions listed on the Indonesia Stock Exchange (IDX). The research population consists of 47 banking firms. A purposive sampling method was applied in selecting the sample. The analysis was conducted using panel regression. The hypothesis testing results reveal that intellectual capital disclosure does not have a significant impact, leverage has a positive and significant effect, while company size negatively influences the financial performance of banks during the 2019–2023 period.